2006
DOI: 10.1016/j.virol.2006.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent HIV-1 Env vaccine formulations delivered by the DNA priming plus protein boosting approach are effective in generating neutralizing antibodies against primary human immunodeficiency virus type 1 isolates from subtypes A, B, C, D and E

Abstract: A major challenge in developing an HIV-1 vaccine is to identify immunogens and their delivery methods that can elicit broad neutralizing antibodies against primary isolates of different genetic subtypes. Recently, we demonstrated that priming with DNA vaccines expressing primary HIV-1 envelope glycoprotein (Env) followed by recombinant Env protein boosting was successful in generating positive neutralizing antibody responses against a clade B primary HIV-1 isolate, JR-FL, that was not easily neutralized. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 73 publications
9
89
1
Order By: Relevance
“…Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26]. Furthermore, when polyvalent primary Env antigen formulations were used, the DNA primeprotein boost approach was more effective than the monovalent primary Env antigen in eliciting rabbit NAbs against a wide range of selected primary viral isolates across subtypes A, B, C, D and E [27]. In the current study, a multi-gene, polyvalent DNA prime-protein boost HIV-1 vaccine was formulated based on the above preclinical study findings, and its immunogenicity was tested in healthy adults in a Phase I clinical trial.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26]. Furthermore, when polyvalent primary Env antigen formulations were used, the DNA primeprotein boost approach was more effective than the monovalent primary Env antigen in eliciting rabbit NAbs against a wide range of selected primary viral isolates across subtypes A, B, C, D and E [27]. In the current study, a multi-gene, polyvalent DNA prime-protein boost HIV-1 vaccine was formulated based on the above preclinical study findings, and its immunogenicity was tested in healthy adults in a Phase I clinical trial.…”
Section: Introductionsupporting
confidence: 57%
“…Individual gp120 antigens (100ng/lane) were subjected to SDS-PAGE and blotted onto PVDF membrane, as previous described [27]. Blocking of PVDF membrane was done with 0.1% I-Block (Tropix, Bedford, MA).…”
Section: Western Blotmentioning
confidence: 99%
“…A stable Chinese Hamster Ovary (CHO) cell line was constructed to express the recombinant gp120-BC protein as previously described. 8 Secreted gp120-BC protein from a stably transfected CHO cell line was harvested and purified by FPLC using Lentil lectin sepharose 4B column (GE Healthcare, Waukesha, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated that priming immunizations with DNA vaccines expressing Env antigens can significantly enhance the quality, especially the neutralizing activities, of antibody responses elicited by subunit Env protein vaccines [7][8][9][10][11] ReseaRcH papeR ReseaRcH papeR of the same subtype and whether the DNA priming step is helpful for further improving the quality of antibody responses.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the results of the human efficacy phase 2b trial HVTN 505, which tested a combination of three envelope (Env) immunogens from different clades as a vaccine, were disappointing 25. The HVTN 505 vaccine included a multivalent (six plasmid) DNA prime, each plasmid expressing either a clade B gag , pol or nef or a clade A, B or C env gene, followed by a boost with four recombinant adenovirus (rAd5) vectors expressing either a clade B Gag/Pol fusion protein, or clade A, B or C Envs.…”
Section: Vaccine Approaches To Contend With Hiv‐1 Diversitymentioning
confidence: 99%